The Work-life Balance Among Private Secondary School Teachers - Sabuero, Jimmy B. (Future Science / FSH-PH Publications, 2024)
The work-life balance emphasizes the relevance of behavioral and psychological development for public and commercial sector workers. It highlights how many workers lack the moral, emotional, and psychological stability for productive work and positive working relationships. It is advised that workers participate in work-life balance programs to help them manage their personal and professional lives. It is essential to comprehend the underlying causes of human attitudes and behaviors and the effects of managerial decisions and the organizational environment. Furthermore, the study used descriptive statistics with 50 faculty and staff through convenient sampling. The instruments also passed through validity and reliability testing. The study reveals that on the demographic profile, there were f=25, 50% of the employees were under probationary; also, it must have f=28, 56% under the tenure of 1-2 years in service to the organization; further, there were f=41; 82% with a salary of 10-20,000 Php, moreover, f=33 or 66% worked teacher. These figures revealed that most of them are establishing individuals. Furthermore, behavioral Management has an M=3.51; SD=.610 as interpreted as a very high work-life balance, while the emotional and psychological has an M=3.44; SD=.593 as interpreted as